2002
DOI: 10.1007/3-540-47906-6_64
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of LEO Satellite Networks

Abstract: Abstract. We present an analytical model for computing call blocking probabilities in a LEO satellite network that carries voice calls. Both satellite-fixed and earth-fixed constellations with inter-orbit links and hand-offs are considered. The model is analyzed approximately by decomposing it into sub-systems. Each sub-system is solved in isolation exactly using a Markov process, and the individual results are combined together through an iterative method. Numerical results demonstrate that our method is accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In [16], it is shown that static routing gives better results than dynamic routing. In [17][18][19] the FSA model is used to calculate the blocking probability. In [20], it is believed that the FSA assumption is not realistic and the path has to do handover in every moment where the underlying network architecture changes due to the satellite motion and the routing must be done according to the probabilistic model that chooses the least probable handover ISLs as the most convenient path.…”
Section: Satellite Networkmentioning
confidence: 99%
“…In [16], it is shown that static routing gives better results than dynamic routing. In [17][18][19] the FSA model is used to calculate the blocking probability. In [20], it is believed that the FSA assumption is not realistic and the path has to do handover in every moment where the underlying network architecture changes due to the satellite motion and the routing must be done according to the probabilistic model that chooses the least probable handover ISLs as the most convenient path.…”
Section: Satellite Networkmentioning
confidence: 99%
“…Earth is divided into cells with users in a cell served by one or more satellites. LEOs are expected to provide wireless mobile communication services from any place to any other place on earth and support wireless communication from and to areas not covered by cellular or geostationary phone systems [5,6].…”
Section: The Concept Of Leo Satellitesmentioning
confidence: 99%
“…LEO satellites can be used to supplement terrestrial networks by providing links between points on the surface that would be difficult or too expensive to connect with terrestrial links. A more ambitious approach is to replace large parts of terrestrial networks by using inter-satellite links to inter-connect a number of satellites into a LEO satellite network, as shown in Figure (3), three satellites in a single orbit connected with ISLs [4,6].…”
Section: The Concept Of Leo Satellitesmentioning
confidence: 99%
See 1 more Smart Citation